PERAN SERTA WARGA MISKIN DALAM PROGRAM KEGIATAN PENANGGULANGAN KEMISKINAN DI KOTA SEMARANG TAHUN 2010 - Rejekiningsih, Tri Wahyu (JURNAL DINAMIKA EKONOMI PEMBANGUNAN, 2011)
Most of the poor in Semarang who is married are about 69 percent with 3 persons of family dependents. 54 percent have their own house where 46 percent do not have it. The poor’s main jobs are mostly as laborers. This is possible because the level of education are very low, there are about 59 percent have only primary school level. These condition will affect the productivity level of the poor so that they earn approximately about Rp 599.405,00 every month. The type of assistance the poor in Semarang received include: food (Raskin), health (Jamkesmas), house and road renovation (PNPM), and liquidity/ money (BLT). The periods of the assistance is once a month, for Raskin, whereas Jamkesmas provides a card for a free medical treatment. The poor knowledge about the criteria of aid receiver is only 30 percent who knew, it means that there are 30 percent of poor people realize that they own the right to receive the aid. This causes the direct involvement level of the poor is very low, at only about 15 percent, while there are about 60 percent stated to not been involved and another 15 percent rarely involved. The form of the involvement are: participate to share or distribute, inform the other resident (notification), collect ID card and family member card of the resident who will get the aid. There are several types of assistance which is considered to accelerate resident alleviation from poverty: cheap food (Raskin), health (Jamkesmas), education (training skills), job opportunities and soft loans (capital bussiness).